HRM: DEVELOPING ORGANIZATIONAL COMMUNICATION CULTURE IN TRANSITIONAL ECONOMIES - Ahmeti, Faruk (European Scientific Journal, ESJ, 2014)
All countries in South Eastern Europe (SEE), in particular countriesemerged from ex-Yugoslavia, are going through the transition process formany years. Switching from one economy to another, from closed andcentralized to open and free market economy, has forced many companies tochange their working and operating culture, especially the communicationculture within human resource management (HRM). Hence, the entireeconomy has started to learn new rules of the global market, new workingculture, and they needed to understand, launch and to execute them,especially undeveloped countries such as Kosovo. Having this in mind, notonly the organizations needed to change, but the most important was thatindividuals within those countries needed to change their working andcommunication culture. According to the conception of staff management,human resource management (HRM) needs well-organized, competent, andefficient use of human resources, which in Kosovo were on hand. In order toensure this, various activities focused towards the area of HRM. Some of themajor activities that were undertaken, and still needs to be improved arerecruitment of employees who possess new skills (such as language,education, etc.), development of skills missing within the market and whichare crucial to survive in the new open market, strengthening of relations andcreating a new one, mutual inspiring, developing new communication culturewithin the organization, implementation of contemporary working processesand developing systems that can be used by individuals or groups to face thenew requirements emerged bay new economic developments.